"They just don't get it!" When family disagrees with expert opinion. Issue 8 (30th July 2009) - Ho, A
Abstract : The notions of "expert" and "expertise" imply that some people have more credibility than others on certain matters. While expert authority is often taken for granted, there are questions as to whether expert power in some cases can be a form of epistemic oppression. Informed by bedside disagreements between family and clinicians as well as feminist discussions of epistemic oppression, this paper argues for a commitment to epistemic humility and the adoption of a two-way collaborative approach between clinicians and families that can help to enhance professionals' own understanding of their theoretical framework and also promote responsive patient care.